2008
DOI: 10.1590/s1519-69842008000500015
|View full text |Cite
|
Sign up to set email alerts
|

The ecological dynamics of Barra Bonita (Tietê River, SP, Brazil) reservoir: implications for its biodiversity

Abstract: Barra Bonita reservoir is located in the Tietê River Basin -São Paulo state -22° 29" to 22° 44" S and 48° 10° W and it is the first of a series of six large reservoirs in this river. Built up in 1963 with the aim to produce hydroelectricity this reservoir is utilized for several activities such as fish production, irrigation, navigation, tourism and recreation, besides hydroelectricity production. The seasonal cycle of events in this reservoir is driven by the hydrological features of the basin with consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 24 publications
3
54
0
7
Order By: Relevance
“…The only site at which a high density of zooplankton was found was near the entrance of the Jaguari river, probably reflecting the higher trophic conditions suggested by the high phosphorus and chlorophyll concentrations (TSI value = 69). The fall in zooplankton at the end of the rainy season has also been observed in other reservoirs, as in the Guarapiranga reservoir, by Sendacz et al (2006), and the Barra Bonita reservoir, by Tundisi et al (2008).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The only site at which a high density of zooplankton was found was near the entrance of the Jaguari river, probably reflecting the higher trophic conditions suggested by the high phosphorus and chlorophyll concentrations (TSI value = 69). The fall in zooplankton at the end of the rainy season has also been observed in other reservoirs, as in the Guarapiranga reservoir, by Sendacz et al (2006), and the Barra Bonita reservoir, by Tundisi et al (2008).…”
Section: Discussionsupporting
confidence: 54%
“…Tundisi et al (2008) indicated that, in the Barra Bonita reservoir, the highest concentration of nutrients occurs at the beginning of the rainfall, due to entrainment of soil particles from runoff and via tributaries; however, after some time, a diluting effect may occurs because of the increased volume of water, reducing the concentration of nutrients. This may explain why, despite the high rates of TSI during the rainy season, caused by the importing of nutrients, zooplankton communities have low densities, possibly due to dilution caused by excess rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Variables associated with anthropogenic activities with impact on water quality were positively correlated. That was the case of the correlation of E.coli density and NO 2 -and SO 4 -2 concentrations, indicating that those environments receive domestic sewage discharge without pretreatment (Tundisi et al, 2008;Zhao et al, 2011). The correlation of COND with NO 2 -may also be an indicative of local human impacts.…”
Section: Discussionmentioning
confidence: 93%
“…Conditions of topography and land use are also important factors that influence the water quality in lotic environments (Sheldon et al, 2012), requiring the use of methods of study that focus both the ecological and anthropogenic processes occurring in the landscape scale and/or in the watershed as a whole (Likens, 1984;Wiens, 1989;Zalewski, 2000;Turner et al, 2001;Tundisi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nothwithstanding the difficulties in establishing the concentration limits which characterize mesotrophic, eutrophic and hypereutrophic conditions (Tundisi et al, 2008) …”
Section: Resultsmentioning
confidence: 99%